Western Elements in the Early Thule Culture of the Eastern High Arctic - Schledermann, Peter; McCullough, Karen M. (ARCTIC, 1980)
Excavations of Thule culture winter sites in the Bache Peninsula region on the east coast of Ellesmere Island have yielded a number of finds which indicate a strong relationship to cultural developments in the Bering Sea region. Specific elements under discussion include dwelling styles, clay pottery, needle cases, a brow band and harpoon heads. Evidence is presented suggesting an initial arrival of the Thule culture Inuit in the eastern Arctic around 1050 A.D.